Thermal simulation experimental study on the difference of molecular structure evolution between vitrinite and inertinite in low-rank coal - Qin, Rongfang; Wang, Lu; Cao, Daiyong; Wang, Anmin; Wei, Yingchun; Li, Jing (Frontiers in Earth Science, 2022)
To carry out an in-depth study of the differences in the molecular structure evolution of the vitrinite and the inertinite during coalification, the chemical structure of 13 groups of vitrinite and inertinite with different coal ranks were comprehensively characterized using X-Ray Diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and 13C nuclear magnetic resonance (13C NMR). The correlation of structure parameters and vitrinite random reflectance (Ro, ran) were analyzed. The results show that three evolution stages of vitrinite were observed with Ro, ran at 0.35–0.90%, 1.20–2.67%, and 3.03–4.20%, and two evolution stages of inertinite were marked with Ro, ran at 0.35–2.07% and 2.07–4.20%. The fa, DOC, I, fa', faH, faN, faB, Xb, La, Lc, and Nave of inertinite are always larger than vitrinite, whereas the A(CH2)/(CH3), fal, fal *, fal H, d002 of inertinite are always smaller than vitrinite. When Ro, ran =0.35%-0.90%, the oxygen-containing functional groups and aliphatic structure of vitrinite fall off rapidly, the condensation degree of the aromatic ring, La, Lc, and Nave increase, while the length of side chains and d002 decrease. When Ro, ran =1.20%-2.67%, the vitrinite structure variation follows the same trend as the first stage, but the evolution rate is significantly lower. When Ro, ran =0.35%-2.07%, the oxygen-containing functional groups, methyl groups, and methylene groups of inertinite fall off at a slower rate than vitrinite. The aromaticity, condensation degree, aromatic carbon content, and order degree of microcrystalline structure also increase at a rate less than that of vitrinite. The vitrinite and inertinite structure variation becomes flat and the structures of both macerals are similar in the high metamorphic stage. The content of oxygen-containing functional groups and aliphatic chain length decrease to the lowest, while the aromaticity increases to the maximum. This study contributes to a comprehensive understanding of the chemical structure differences between vitrinite and inertinite, which can provide a theoretical reference for the clean utilization of coal and coalbed methane (CBM) exploration and development.